The drinking water handbook - Spellman, Frank R.; Drinan, Joanne (Boca Raton, FL. : CRC Press, 2012)
'The Drinking Water Handbook is a systematic explanation of the many processes employed to make water safe to drink. It clarifies the laws that set the standards for quality and investigates the physical, chemical and microbiological parameters that must be modified to produce potable and good-tasting water. Careful attention is paid to present and emerging technologies that result in high-quality drinking water: purification, filtration, disinfection, distribution, and more. The book discusses the relation of water reuse to the hydrologic cycle and explains what is being done to mitigate growing concerns about disinfection by-products'--
'An industry-wide best-seller hailed on its first publication as a masterly account written in an engaging, highly readable style, The Drinking Water Handbook, 2nd ed., continues where the first edition began; that is, stressing that notwithstanding our absolute need to breathe untainted air, nothing is more important to us than the quality of the water we drink, though of course, we need clean water for other uses as well. Written with the practitioner, novice and the sophisticated consumer in mind, this new edition of The Drinking Water Handbook has been thoroughly revised and updated, including a comprehensive discussion of security requirements for waterworks and ancillary processes.'--
Includes bibliographical references and index.
Keywords: Water quality management -- Handbooks, manuals, etc; Drinking water -- Handbooks, manuals, etc